A murderous mind : a Naomi Blake novel - Adams, Jane, 1960- (Adams, Jane, 1960- Naomi Blake mysteries., 2015)
The murder of a student re-opens a series of cold cases in this intriguing mystery. A young student is found brutally murdered in her room, killed while her flatmates slept nearby. The police soon recognize that this is frighteningly similar to a crime committed fifteen years before. A crime investigated by the now discredited Detective Inspector Joe Jackson, but never solved. Other deaths, linked to the same modus operandi and stretching back more than twenty years, have also remained unsolved. No link has been found between the victims - but it seems Joe Jackson had a perpetrator in mind. He had however been unable to prove his guilt. Can the new investigation trust the judgement of a man who was himself a killer? Or did that give Naomi Blake's one-time friend and mentor an insight his colleagues did not have?